(3GdJQHjI hJMhdGJ YUQ GdYhdeI; eOGNd ddfbO hGdGSJTQGas - (3eMSf, eUWais ((3HjQhJs (3GdeQcR GdKbGaj GdYQHjs, 2004)
(3jVe gPG GdcJGH CQHY eSGgeGJ jYJHQ GdbGSe GdeTJQc HjfgG cRfgG JJeMhQ, HGdCSGS Mhd eYGdLI HYV LhGfH hechfGJ GdCReI GdJQHhjI aj eLJeYGJfG, hWfjkG hYQHjkG hKGdKjkG, hNGUI aj gPG GdYgO GdYhdeI GdLOjO GdehShe HGdcKjQ ef YfGUQ GdUQGY hGdZehV hGdahVi hGdJfGbVGJ hGdQgGfGJ hHhDQ GdJhJQ hGdJMce hGdGSJbWGH(B... (3GdN, hbO MGhd GdHGMK aj Ld gPg GdeSGgeGJ, EHQGR Cge CHYGO hLPhQ hechfGJ hJLdjGJ hYhGbH(B... (3gPg GdCReI GdePchQI(B. (3hPdc HZQV CWQGM HYV GdCSFdI hGdJSGDdGJ, haJM HYV GdBaGb, hGbJQGM HYV GdHOGFd hGdBdjGJ hGdeecfGJ GdeJGMI dEYGOI GdfXQ aj ChVGYfG GdJQHhjI hGdGLJeGYjI GdeCRheI HgOa GdEUdGM hGdJMOjK hGdJWhjQ, GfWdGbkG ef QDjI hGVMI ddeSJbHd heTQhY eLJeYj hMVGQj eJejR, eJcGed hehLg, hHMKkG Yf GdecGfI hGdOhQ hGdaGYdjI GdeYQajI hGdJGQjNjI aj YGde eJMhd, SQjY GdJLOO, HGdZ GdJTGHc hGdJYbjO(B: (3eQLYjGJ hCSSkG heYGjjQ hCfSGb bje hefXheGJ eYQajI hGLJeGYjI hMVGQjI hYbGFOjI eJYOOI(B... (3hgcPG jJfGhd GdaUd GdChd YdGbI GdJQHjI HGdYhdeI ef NdGd efGbTI fbOjI dCWQhMI (B"(3fgGjI GdJQHjI(B" (3Ch (B"(3fgGjI GdeOQSI GdhWfjI(B"(3, ceG JQhL dgG HYV GdNWGHGJ GdYhdeI GdLOjOI GdeQSheI HeG CUHM jOYj H`(B:"(3NWGH GdfgGjI(B" (3GdPj CSS dg ahchjGeG hWhQg HYV CfUGQg heQjOjg(B. (3hbO GfUH aj gPg GdefGbTI, Ydi eMGhdI bQGAI fbOjI dHYV CHYGO GdeYbhd hGddGeYbhd, hGdeYQaj, hGdEjOjhdhLj, hGdXGgQ hGdeVeQ aj gPg GdNWGHGJ GdeYfjI(B. (3CeG GdaUd GdKGfj abO YGdL ajg eG ZOG YfOfG ehShekG H`(B"(3GdCReI GdJQHhjI(B" (3hPdc ef efXhQ ShSjhdhLj fbOj jQhe JbOje JMdjd eJcGed debheGJgG hechfGJgG hEMGdJgG GdeQLYjI(B... (3ceG jQej Edi hVY HYV GdebOSGJ GdCSGSjI dELGHI YbdGfjI hhGbYjI Ydi eG CUHM jWQMg YdjfG (B"(3SDGd GdEUdGM GdJQHhj(B"(3, hdG SjeG aj Ref GdYhdeI GdRGMaI HfG hYdjfG ef bVGjG hETcGdGJ, hef EecGfjGJ heTGQjY hBaGb ddJLGhR hGdJNWj(B. (3hCeG GdaUd GdKGdK hgh aj eVehfg MhGQ Ph WGHY acQj YGe abO YGdL GdETcGdjI GdJj Je JfGhdgG aj GdaUd GdBfa JMOjOkG, eY GdGgJeGe HEYWGFgG gfG CHYGOkG ShSjhMVGQjI hWfjI hbhejI YQHjI hESdGejI, Hd hKGdKjI CjVkG(B. (3ceG bOe aj HYV eMGhQ gPG GdaUd eG jecf JhUjag H`(B"(3ebOeGJ Ch eOGNd(B" (3dbQGAI hage Cge GdeVGejf hGdJhLgGJ GdacQjI hGdSjGSjI hGdJQHhjI hGdGLJeGYjI(B... (3GdeDSSI deQLYjI (B"(3GdejKGb GdhWfj ddJQHjI hGdJchjf(B"(3, heG jJWdHg GSJKeGQg hCLRGFg hJaYjd ehGOg hHfhOg hJWHjbg GdYedj ef hYj fbOj Tehdj, hEOQGc QDjhj Yejb dEcQGgGJ hQhgGfGJ hedGHSGJ heTcdGJ hNUhUjGJ hTQhW XQajJfG GdQGgfI aj GQJHGWGJgG GdeMdjI hGdOhdjI, heG jecf Cf jchf dPdc ef BKGQ heSJJHYGJ YdJ eSGQ eTQhY GdEUdGM GdJQHhj GdefThO, CjVkG gh GdCeQ HGdfSHI dfehPL GdeZQH(B. (3hGfWdGbkG ef efWb GSJfJGLj JOQLj jYJeO CSdhH GdGfJbGd ef GdYGe Edi GdNGU, LYd ef ehVhY GdaUd GdQGHY ebGQHI ChdjI dbVjI LRFjI eeG hQO aj (B"(3GdejKGb GdhWfj ddJQHjI hGdJchjf(B" (3hgj bVjI Jqe GdETGQI EdjgG HEjLGR aj GdaUd(B/(3GdMhGQ GdYGe GdSGHb, CdG hgj (B"(3GdeSCdI GddZhjI(B" (3Hcd CHYGOgG heOdhdGJgG GdJQHhjI hGdKbGajI hGdGLJeGYjI GdeJYOOI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Educational prospective; Prospective; (3GdGSJTQGas